Production of magnetic biochar from waste-derived fungal biomass for phosphorus removal and recovery - Jack, Joshua; Huggins, Tyler M.; Huang, Yingping; Fang, Yanfen; Ren, Zhiyong Jason (Journal of cleaner production, 2019)
This study presents a new bottom-up biofabrication method to produce highly porous magnetic biochar from waste-derived fungal biomass. Neurospora crassa was grown in iron containing coagulation backwash (BW) diluted with primary effluent (PE) wastewater in two ratios of 1:4 (PE-BW 1:4) and 3:4 (PE-BW 3:4). The fungi encapsulated iron directly into biomass hyphae and carbonization resulted in one-step biochar preparation and maghemite (Fe2O3) formation. The morphology and structure of the materials were investigated using a suite of characterization tools. Results indicated that the physiochemical properties of each char were dependent on the blend used for fungal cultivation. PE-BW 1:4 had much larger average pore diameters (13.2 nm vs. 6.1 nm), less elemental surface carbon (2.1% vs. 23.7%), and more expansive Fe2O3 formation. Batch phosphorus adsorption experiments were conducted in the range of 0–90 mg-P/L, and a maximum adsorption density of 23.9 mg/g was achieved. Langmuir, Freundlich and Temkin isotherms were used to describe the interactions of the phosphate on the absorbents and an in-depth error analysis was conducted. Further characterization of the P-loaded chars indicated adsorption primarily via P-OH bonding on the surface of the materials. This new biofabrication method showed great potential to magnetic biochar production with excellent phosphorus adsorption, which can be effectively used in wastewater resource recovery. •Fungi (N.crassa) can be used as a feedstock for direct magnetic biochar production.•Physiochemical properties of biochar are dependent on the fungal growth conditions.•Fungal biochar effectively adsorbed phosphorus from aqueous solution.